2020
DOI: 10.1097/ccm.0000000000004748
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly High Frequency of Enterococcal Bloodstream Infections in Coronavirus Disease 2019 Patients Admitted to an Italian ICU: An Observational Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
89
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 29 publications
(31 reference statements)
15
89
2
1
Order By: Relevance
“…Bacterial superinfection with Staphylococcus is a long-recognized consequence of influenza and important cause of morbidity and mortality ( 6 , 7 ), so further studies will be useful to determine if similar mechanisms operate during COVID-19. We also noted several patients with high relative abundances of Enterococcus , which was recently described as a common cause of bloodstream infection in critically ill COVID-19 patients ( 40 ).…”
Section: Discussionsupporting
confidence: 56%
“…Bacterial superinfection with Staphylococcus is a long-recognized consequence of influenza and important cause of morbidity and mortality ( 6 , 7 ), so further studies will be useful to determine if similar mechanisms operate during COVID-19. We also noted several patients with high relative abundances of Enterococcus , which was recently described as a common cause of bloodstream infection in critically ill COVID-19 patients ( 40 ).…”
Section: Discussionsupporting
confidence: 56%
“…A large multi-centric cohort study including only COVID-19 highlighted that the most common presumed source was unknown or not reported [ 30 ]. Moreover, the role of bacterial translocation should further be evaluated: a recent monocentric Italian study showed an increased risk for enterococcal BSI among COVID-19 patient, thus suggesting an enteric involvement in patients with severe COVID-19 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intensive care unit studies in Italy demonstrated an increase in the rate of infections by Klebsiella carbapenemase-resistant, E. coli , and Enterococcus spp., but these studies considered both COVID-19 and no COVID-19 patients [ 24 , 25 ]. Conversely, in a Spanish study carried out in a tertiary hospital for 20 weeks before and during the COVID-19 spread, the mean incidence density of blood infections caused by MDR organisms remained stable, with a value of 0.36 ± 0.42 cases per 1000 occupied bed days in the COVID-19 period and 0.33 ± 0.28 bloodstream infections per 1000 occupied bed days in the period before the national lockdown [ 26 ].…”
Section: Discussionmentioning
confidence: 99%